2019
DOI: 10.7717/peerj.6369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size on physicochemical and functional properties of superfine black kidney bean (Phaseolus vulgaris L.) powder

Abstract: Black kidney bean (Phaseolus vulgaris L.) powder (BKBP) with particle sizes of 250–180, 180–125, 125–75, 75–38, and <38 μm was prepared by using coarse and eccentric vibratory milling, respectively. Physicochemical properties, cholesterol adsorption, and antioxidant activities of powders were investigated. Size and scanning electron microscopy analyses showed that particle size of BKBP could be effectively decreased after the superfine grinding treatment, and the specific surface area was increased. Flow prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 54 publications
5
15
0
Order By: Relevance
“…It was observed that the lightness (L) rised with reduction in particle size and fine flour with particle size 74 μm showed the highest L value of 88.85. Similar results showing increase in L value have been reported for the rice flour and black kidney bean powder samples by Kim and Shin, 2014;Ahmed et al, 2015 andSun et al, 2019, respectively. This increase in L values has been linked with increase in surface area of fine samples as a result of which more reflection of light takes place.…”
Section: Colorimeter and Phsupporting
confidence: 87%
See 2 more Smart Citations
“…It was observed that the lightness (L) rised with reduction in particle size and fine flour with particle size 74 μm showed the highest L value of 88.85. Similar results showing increase in L value have been reported for the rice flour and black kidney bean powder samples by Kim and Shin, 2014;Ahmed et al, 2015 andSun et al, 2019, respectively. This increase in L values has been linked with increase in surface area of fine samples as a result of which more reflection of light takes place.…”
Section: Colorimeter and Phsupporting
confidence: 87%
“…This decrease in bulk density was significant from 249 μm to 211 μm and became insignificant with further reduction in particle size. However, Sun et al (2019) had reported a decline in bulk density from 0.439 g/mL to 0.364 g/mL as the flour particle size reduced from 250-180 μm to <38 μm for black kidney bean powder. Ahmed et al (2015) found no significant changes in the bulk density of the rice flour samples with change in particle size, and reported that the significant decrease occurred only for finest particle size flour (74 μm).…”
Section: Bulk Density and Tapped Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The percentile values demonstrated that the large particle sample gave big granules than that of samples with small particle size, which trend was similar to the previous research (Ma and Mu, 2016;Sun et al, 2019).…”
Section: Resultssupporting
confidence: 90%
“…The use of coarse bulking agents is desirable because previous results indicated that their use increases the yield and survival of insects (Artiaga-López et al ., 2018). Moreover, they promote an increment in nutrient absorption rates when modifying texture, wetness, consistency, hardness, distribution, water availability, biochemical stability, and bioavailability compounds, as well as the palatability of the diet (Bhattacharya and Waldbauer, 1970; Lingappa, 1987; Aguilera, 2005; Parada and Aguilera, 2007; Tomic-Carruthers, 2007; Sun et al ., 2019). Diet consistency is also relevant because most insects require specific water levels with adequate viscosity.…”
Section: Introductionmentioning
confidence: 99%